Ziziphora tenuior L. essential oil from Dana Biosphere Reserve (Southern Jordan); Chemical characterization and assessment of biological activities. (24th December 2016) - Abu-Darwish, M.S.; Cabral, C.; Gonçalves, M.J.; Cavaleiro, C.; Cruz, M.T.; Paoli, M.; Tomi, F.; Efferth, T.; Salgueiro, L.
Abstract: Ethnopharmacologic relevance: Ziziphora tenuior L. (Lamiaceae) is a medicinal plant in Jordan, which is included in various antimicrobial, antiseptic, expectorant and wound healing preparations. It is used for the treatment of cough, stomach ache, dysentery, fever, uterus infection, gut inflammation and painful menstruation. Aim of the study: The aim of this study was to assess, for the first time, the chemical composition of the essential oil of Z. tenuior originated from southern Jordan and its antifungal effects against several yeasts. Concomitantly, the mechanisms behind the anti-fungal activity against Candida albicans were also disclosed. Since the Z. tenuior traditional uses are related with inflammatory-associated conditions, the putative anti-inflammatory activity of the oil was also unveiled. Importantly, the potential toxicity of pharmacologically active concentrations was screened in different types of mammalian cells. Materials and methods: Z. tenuior essential oil, isolated by hydrodistillation, was analyzed by gas chromatography, gas chromatography–mass spectrometry and 13 C nuclear magnetic resonance spectroscopy. Antifungal activity was evaluated against yeasts, dermatophytes and Aspergillus strains. Germ tube inhibition and biofilm formation assays were evaluated using C. albicans . Assessment of cell viability was made by the MTT assay using different types of mammalian cells, including hepatocytes, keratinocytes and macrophages. The in vitro anti-inflammatory potential of the oil was evaluated by measuring nitric oxide production using lipopolysaccharide-stimulated mouse macrophages. Results: Oxygen-containing monoterpenes are the main oil compounds: pulegone (46.8%), p -menth-3-en-8-ol (12.5%), isomenthone (6.6%) and 8-hydroxymenthone (6.2%). The highest antifungal activity was against Cryptococcus neoformans, with a MIC value of 0.16 µL/mL. The oil revealed an important inhibitory effect on germ tube formation with a filamentation inhibition rate higher than 80% at 0.16 µL/mL. The amount of the attached biomass was reduced. Importantly, concentrations devoid of toxicity on several mammalian cell types still displayed anti-inflammatory activity (0.16 and 0.32 µL/mL). Conclusions: These findings add significant information to the pharmacological activity of Z. tenuior, thus justifying and reinforcing the use of this plant in traditional medicine. Additionally, the antifungal and anti-inflammatory potential of the oil at non-toxic concentrations, opens new avenues for its further exploitation, for instance in health-care product development. Graphical abstract: